Defense Compounds Rather Than Nutrient Availability Shape Aggressiveness Trait Variation Along a Leaf Maturity Gradient in a Biotrophic Plant Pathogen - Maupetit, Agathe; Larbat, Romain; Pernaci, Michaël; Andrieux, Axelle; Guinet, Cécile; Boutigny, Anne-Laure; Fabre, Bénédicte; Frey, Pascal; Halkett, Fabien (Frontiers in Plant Science, 2018)
Foliar pathogens face heterogeneous environments depending on the maturity of leaves they interact with. In particular, nutrient availability as well as defense levels may vary significantly, with opposing effects on the success of infection. The present study tested which of these factors have a dominant effect on the pathogen’s development. Poplar leaf disks of eight maturity levels were inoculated with the poplar rust fungus Melampsora larici-populina using an innovative single-spore inoculation procedure. A set of quantitative fungal traits (infection efficiency, latent period, uredinia size, mycelium quantity, sporulation rate, sporulation capacity and spore volume) was measured on each infected leaf disk. Uninfected parts of the leaves were analyzed for their nutrient (sugars, total C and N) and defense compounds (phenolics) content. We found that M. larici-populina is more aggressive on more mature leaves as indicated by wider uredinia and a higher sporulation rate. Other traits varied independently from each other without a consistent pattern. None of the pathogen traits correlated with leaf sugar, total C, or total N content. In contrast phenolic contents (flavonols, hydroxycinnamic acid esters and salicinoids) were negatively correlated with uredinia size and sporulation rate. The pathogen’s fitness appeared to be more constrained by the constitutive plant defense level than limited by nutrient availability, as evident in the decrease in sporulation.